Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To solve the inequality \((x+2)(x-3)(x+8) \leq 0\), let's go through a step-by-step process:
1. Identify the critical points:
The inequality changes its behavior at the values of \(x\) where the expression equals zero. Solve for the roots of the equation:
[tex]\[ (x+2)(x-3)(x+8) = 0 \][/tex]
The critical points are:
[tex]\[ x = -2, x = 3, x = -8 \][/tex]
2. Determine the intervals:
These critical points divide the number line into four intervals:
[tex]\[ (-\infty, -8), (-8, -2), (-2, 3), (3, \infty) \][/tex]
3. Test the sign of the expression in each interval:
Choose test points from each interval:
- For \((- \infty, -8)\), use \(x = -9\):
[tex]\[ (-9+2)(-9-3)(-9+8) = (-7)(-12)(-1) = -84 \quad \text{(negative)} \][/tex]
- For \((-8, -2)\), use \(x = -5\):
[tex]\[ (-5+2)(-5-3)(-5+8) = (-3)(-8)(3) = 72 \quad \text{(positive)} \][/tex]
- For \((-2, 3)\), use \(x = 0\):
[tex]\[ (0+2)(0-3)(0+8) = (2)(-3)(8) = -48 \quad \text{(negative)} \][/tex]
- For \((3, \infty)\), use \(x = 4\):
[tex]\[ (4+2)(4-3)(4+8) = (6)(1)(12) = 72 \quad \text{(positive)} \][/tex]
4. Include the endpoints where the expression is zero:
Since the inequality is \(\leq 0\), include the points where the expression is exactly zero:
[tex]\[ x = -8, x = -2, x = 3 \][/tex]
5. Combine the intervals where the expression is negative or zero:
The expression \((x+2)(x-3)(x+8) \leq 0\) holds in the intervals where we found either a negative value or zero:
[tex]\[ (-\infty, -8] \cup [-2, 3] \][/tex]
So, the solution to the inequality \((x+2)(x-3)(x+8) \leq 0\) is:
[tex]\[ \boxed{(-\infty, -8] \cup [-2, 3]} \][/tex]
1. Identify the critical points:
The inequality changes its behavior at the values of \(x\) where the expression equals zero. Solve for the roots of the equation:
[tex]\[ (x+2)(x-3)(x+8) = 0 \][/tex]
The critical points are:
[tex]\[ x = -2, x = 3, x = -8 \][/tex]
2. Determine the intervals:
These critical points divide the number line into four intervals:
[tex]\[ (-\infty, -8), (-8, -2), (-2, 3), (3, \infty) \][/tex]
3. Test the sign of the expression in each interval:
Choose test points from each interval:
- For \((- \infty, -8)\), use \(x = -9\):
[tex]\[ (-9+2)(-9-3)(-9+8) = (-7)(-12)(-1) = -84 \quad \text{(negative)} \][/tex]
- For \((-8, -2)\), use \(x = -5\):
[tex]\[ (-5+2)(-5-3)(-5+8) = (-3)(-8)(3) = 72 \quad \text{(positive)} \][/tex]
- For \((-2, 3)\), use \(x = 0\):
[tex]\[ (0+2)(0-3)(0+8) = (2)(-3)(8) = -48 \quad \text{(negative)} \][/tex]
- For \((3, \infty)\), use \(x = 4\):
[tex]\[ (4+2)(4-3)(4+8) = (6)(1)(12) = 72 \quad \text{(positive)} \][/tex]
4. Include the endpoints where the expression is zero:
Since the inequality is \(\leq 0\), include the points where the expression is exactly zero:
[tex]\[ x = -8, x = -2, x = 3 \][/tex]
5. Combine the intervals where the expression is negative or zero:
The expression \((x+2)(x-3)(x+8) \leq 0\) holds in the intervals where we found either a negative value or zero:
[tex]\[ (-\infty, -8] \cup [-2, 3] \][/tex]
So, the solution to the inequality \((x+2)(x-3)(x+8) \leq 0\) is:
[tex]\[ \boxed{(-\infty, -8] \cup [-2, 3]} \][/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.